Intercommunal justice in the Aymara communities of the southern Andean region: (First part) - Peña Jumpa, Antonio (2002)
In its simplest meaning, justice is the march or materialization of the resolution of conflicts of a certain social group or community. In accordance with this definition, the following pages want to show and reflect on how a group of conflicts are resolved in an intercommunal or external relationship within a group of Aymara communities in the South Andean region of Peru.